A new electrochemical sensor with the Refreshable Silver Liquid Amalgam Film multi-Electrode for sensitive voltammetric determination of vitamin K2 (menaquinone). (1st March 2018) - Jedlińska, Katarzyna; Strus, Magdalena; Baś, Bogusław
Abstract: This paper presents the first report on design and application of the Refreshable Silver Liquid Amalgam Film multi-Electrode (RAgLAFm-E) for sensitive voltammetric determination of vitamin K2 ( VK2). The sensor consists of the specially constructed silver based Liquid Amalgam Film multi-Electrode (AgLAFm-E) and its body is filled with 1 wt% silver liquid amalgam drop, ca. 20 μL. Construction of the electrode allows fast and simple mechanical liquid amalgam film refreshment before each measurement, which ensures good repeatability and reproducibility of the electrode surface. The RAgLAFm-E was employed in investigation of the electrochemical behavior of VK2 using cyclic voltammetry (CV). The influence of various factors such as the supporting electrolyte composition, instrumental parameters and accumulation conditions, were studied with differential pulse adsorptive stripping voltammetry (DP AdSV). The best results were recorded in the supporting electrolyte containing 70% of methanol, 0.3 M acetic buffer (pH 3.8) and 0.2 M sodium perchlorate, with the scanning performed in the range from −0.04 to −0.40 V, in both cathodic and anodic directions. The anodic peak current, for 30 s of accumulation time, was proportional to the concentration of VK2 in the range of 0.2–8.0 μg L −1  (R = 0.9987) and 4–20 μg L −1  (R = 0.9959) with the limit of detection (LOD, S/N = 3) of 0.009 and 0.012 μg L −1, respectively. The developed method has been successfully applied for quantitative analysis of VK2 in pharmaceutical, microbiological and food samples by the standard addition method. Therefore, the RAgLAFm-E sensor can hold great promise for fast, simple and sensitive determination of VK2 in various real samples.